Beyond the people : social imaginary and constituent imagination - Oklopcic, Zoran (Oxford : Oxford University Press, 2018)
'Beyond the People' develops a provocative, interdisciplinary, and meta-theoretical critique of the idea of popular sovereignty. It asks simple but far-reaching questions: Can 'imagined' communities, or 'invented' peoples, ever be theorized without, at the same time, being re-imagined and re-invented anew? Can polemical concepts, such as popular sovereignty or constituent power, be theorized objectively? If, as this book argues, the answer to these questions is no, theorists who approach the figure of a sovereign people must acknowledge that their activity is inseparable from the practice of constituent imagination. Though widely accepted as important, even vital, for the development of political concepts, the social practice of imagination is almost always presumed to operate either historically or impersonally, but seldom individually.
Previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on June 7, 2018).
Keywords: Democracy -- Philosophy; Self-determination, National -- Philosophy; Sovereignty -- Philosophy; Politics and Government; Politics & government